Drug trafficking and community self-defense in “Tierra Caliente”, Michoacan, Mexico - Fuentes-Díaz, Antonio (Universidad Autónoma de Tamaulipas, 2015)
The violence experienced in different regions of Mexico, and which has been exacerbated particularly in the State of Michoacán, has triggered the formation of the so-called self-defense groups. The aim of this paper was to analyze the characteristics of the emergence and operation of activities of self-defense in the communities of the Ruana and Tepalcatepec, located in the region known as Tierra Caliente, in the State of Michoacan, Mexico. Data presented in the article were obtained from two fieldwork trips made during 2014, where eleven people were interviewed: two members of the movement of self-defense and nine political and social leaders of the communities. Evidence was also collected at a public meeting, where five leaders of the self-defense groups participated. The results reveal that the formation of community self-defense groups was triggered by the breakdown in the local order. Such breakdown was caused by a new form of operation of drug trafficking groups, based on extortion revenue and an excessive control over the region, which in turn had an influence on the balance of local power and tolerance towards illegal activities. The Government’s response was the legalization of these groups through the formation of a rural police force. This new police force has been questioned by members of self-defense groups, who have rejected such a move, holding that such legalization is a replacement of beneficiaries of illegal activities. Self-defense movement refers to a recomposition in the balance of local power relations between drug trafficking, communities and State. It represents a dispute for the establishment of an order that retracts the aggression to the communities and recomposes illegal business operation with new actors and in a less invasive manner.Archive XML (SciELO)